PENCEMARAN SODIUM DODECYLBENZENE SULFONATE (SDBS) PADA IKAN AIR TAWAR: PENENTUAN AKUMULASI DAN MONITORING PENCEMARAN - Monica Cahyaning Ratri (Sanata Dharma University, 2017)
The research for accumulation determination and monitoring of Sodium Dodecylbenzene Sulfonate (SDBS) contamination in freshwater fish has been conducted. The aims of this research were to determine the interference of protein and ions in analysis, the parameters of validation, the correlation of SDBS concentration in the basin and SDBS accumulation in catfish followed by SDBS analysis in freshwater fish that sold in market in the area of Yogyakarta city. This research was started by isolating SDBS from freshwater fish using soxhlet extraction method and then followed by analysis of SDBS using spectrophotometer UV-Vis with acridine orange (AO) reagent. The results showed that the presence of proteins might be interferre the analysis process, Ca2+ and Mg2+ ions might interfere the analysis process at concentrations 12 mg/L and 6 mg/L. Analytical method validation was performed and showed correlation coefficient values (r) was 0,9981, limit of detection was 0,089 mg/L, limit of quantification was 0,0296 mg/L, RSD 2% and % recovery between 83-107%. The content of the SDBS in fish increased with increasing concentrations of SDBS in water and caused the decrease of Bio-concentration Factor (BCF) value. The concentration of SDBS in the analysis of fish in the market were between 0,0012-0,0029 mg/g, 0,0038-0,0077 mg/g and 0.0008-0,0026 mg/g for catfish, red tilapia and carp, respectively.